ORIGINAL RESEARCH - Sânziana Ionescu; Petre Radu; Octavia Luciana Madge; Victor Strâmbu (Oncolog-Hematolog.ro)
Preliminary results of markers as predictors for the tissue response to radiochemotherapy in rectal cancer